Bending Performance of Timber Beam Strengthened with Passive Prestressing - Yeoh, David; Leng, Violet; Jamaluddin, Norwati; Heng Boon, Koh; Jamalaldin, Seyed; Tighnavard, Ali; Abd Ghafar, Nor Hayati (International Journal of Sustainable Construction Engineering and Technology, 2023)
Prestressing technology and its application is common in concrete design and construction particularly in Malaysia and most parts of the world. However, prestress strengthening in timber is rare and not widely applied especially in Malaysia. Application of prestressing in timber has the potential to allow the use of longer span with reduced cross-sectional size and simultaneously exhibiting some level of ductility through the prestressing rod since timber material is susceptible to brittle tensile failure. This paper highlights exploratory research into the extent of bending performance enhancement in Malaysian Kempas species timber beam strengthened by way of passive prestressing. The research was conducted to investigate the change in bending strength and moment capacity of timber beam with passive prestressing rods installed at different lever arm positions, and the enhancement of moment capacity of timber beam with and without passive prestressing.  Five Kempas timber specimen configurations with size of 40 mm (b) × 90 mm (d) × 900 mm (l) were prepared for four-point bending tests, and their bending behaviours were evaluated. The timber beam with passive prestressing steel rods applied at tension side bottom fibre of timber beam exhibited the greatest enhancement in bending performance and stiffness. The improvement of bending performance ranges from 1.1 to 1.5 times greater compared to the timber beam without prestressing steel rods. The improvement of stiffness in prestressed timber beam is up to 11% at service limit state and a reduced rate of stiffness degradation is prominent.